ALM Fluid Therapy Shifts Sympathetic Hyperactivity to Parasympathetic Dominance in the Rat Model of Non-Compressible Hemorrhagic Shock. Issue 2 (February 2022) - Letson, Hayley L.; Biros, Erik; Morris, Jodie L.; Dobson, Geoffrey P.
Abstract : ABSTRACT: Excessive sympathetic outflow following trauma can lead to cardiac dysfunction, inflammation, coagulopathy, and poor outcomes. We previously reported that buprenorphine analgesia decreased survival after hemorrhagic trauma. Our aim is to examine the underlying mechanisms of mortality in a non-compressible hemorrhage rat model resuscitated with saline or adenosine, lidocaine, magnesium (ALM). Anesthetized adult male Sprague-Dawley rats were randomly assigned to Saline control group or ALM therapy group (both n = 10). Hemorrhage was induced by 50% liver resection. After 15 min, 0.7 mL/kg 3% NaCl ± ALM intravenous bolus was administered, and after 60 min, 0.9% NaCl ± ALM was infused for 4 h (0.5 mL/kg/h) with 72 h monitoring. Animals received 6–12-hourly buprenorphine for analgesia. Hemodynamics, heart rate variability, echocardiography, and adiponectin were measured. Cardiac tissue was analyzed for adrenergic/cholinergic receptor expression, inflammation, and histopathology. Four ALM animals and one Saline control survived to 72 h. Mortality was associated with up to 97% decreases in adrenergic (β-1, α-1A) and cholinergic (M2) receptor expression, cardiac inflammation, myocyte Ca 2+ loading, and histopathology, indicating heart ischemia/failure. ALM survivors had higher cardiac output and stroke volume, a 30-fold increase in parasympathetic/sympathetic receptor expression ratio, and higher circulating adiponectin compared to Saline controls. Paradoxically, Saline cardiac adiponectin hormone levels were higher than ALM, with no change in receptor expression, indicating intra-cardiac synthesis. Mortality appears to be a "systems failure" associated with CNS dysregulation of cardiac function. Survival involves an increased parasympathetic dominance to support cardiac pump function with reduced myocardial inflammation. Increased cardiac α-1A adrenergic receptor in ALM survivors may be significant, as this receptor is highly protective during heart dysfunction/failure. Abstract : Supplemental Digital Content is available in the text